A Multi‐Wall Sn/SnO2@Carbon Hollow Nanofiber Anode Material for High‐Rate and Long‐Life Lithium‐Ion Batteries. (17th January 2020) - Gao, Songwei; Wang, Nü; Li, Shuai; Li, Dianming; Cui, Zhimin; Yue, Guichu; Liu, Jingchong; Zhao, Xiaoxian; Jiang, Lei; Zhao, Yong
Abstract: Multi‐wall Sn/SnO2 @carbon hollow nanofibers evolved from SnO2 nanofibers are designed and programable synthesized by electrospinning, polypyrrole coating, and annealing reduction. The synthesized hollow nanofibers have a special wire‐in‐double‐wall‐tube structure with larger specific surface area and abundant inner spaces, which can provide effective contacting area of electrolyte with electrode materials and more active sites for redox reaction. It shows excellent cycling stability by virtue of effectively alleviating pulverization of tin‐based electrode materials caused by volume expansion. Even after 2000 cycles, the wire‐in‐double‐wall‐tube Sn/SnO2 @carbon nanofibers exhibit a high specific capacity of 986.3 mAh g −1 (1 A g −1 ) and still maintains 508.2 mAh g −1 at high current density of 5 A g −1 . This outstanding electrochemical performance suggests the multi‐wall Sn/SnO2 @ carbon hollow nanofibers are great promising for high performance energy storage systems. Abstract : Draht in der Röhre : Hohle mehrwandige Sn/SnO2 @Kohlenstoff‐Kompositnanofasern wurden durch Elektrospinnen und Karbonisationsreduktion hergestellt. Sie haben einen festen, drahtförmigen Kern, der von einer doppelwandigen Röhre umhüllt ist. Das Material weist eine hohe Energiedichte und Zyklenstabilität auf und zeigt eine überlegene elektrochemische Leistung, mit einer Kapazität von 986.3 mAh g −1 bei 1 A g −1 und 508.2 mAh g −1 bei 5 A g −1 nach 2000 Zyklen.